Pembangunan Infrastruktur Pendidikan Dalam Pemindahan Ibukota Negara Di Indonesia - Maksum, Muh. Nur Rochim; Ramdhani, Deddy; Fatimah, Meti; Nisa, Athia Tamyizatun (Universitas Muhammadiyah Yogyakarta, 2022)
The discussion about IKN is generally dominated by government infrastructure planning. There has been no more detailed discourse on how to build the educational infrastructure. Whereas in its history, the capital has played an important role in developing education. This paper uses a literature approach, with the method of description and analysis. The results of the discussion are that 1) moving the capital is a common thing in history, but there are differences in social context between the past and the present, 2) Infrastructure development usually follows the needs of the community, 3) The need for educational infrastructure must be provided at the age of compulsory education at the location IKN, 4) Educational infrastructure is not only carried out by the Government, but must cooperate with private educational institutions, both public and religious.